Sejarah yang Terlupakan: Pentingnya Kesadaran Sejarah dalam Pembelajaran Sejarah - Hasana, Fauziatul; Bahri, Bahri (Lembaga Intelektual Muda Maluku, 2025)
This study aims to analyze the importance of historical awareness in history learning in schools. This study uses the literature study method (library research) to examine the importance of historical awareness in history learningData was collected from various written sources, such as textbooks, scientific journals, academic articles, research reports, and official documents that discuss the concept of historical awareness and historical learning practices. Source selection is carried out selectively based on relevance to the research topic, source validity, and completeness of information. Data analysis is carried out qualitatively by identifying key ideas, comparing various views, and formulating a synthesis of thoughts. The results of the data analysis show that if the awareness of education can be developed through social learning that is based on historical, social and cultural experiences as teachers in improving the awareness of social and educational education.